Answer:
Solving the given linear system, we get x = 1 and y = -3.
The solution set is: (1,-3)
Step-by-step explanation:
We need to solve the linear system of equations.
[tex]3x-y=6 \\y=x-4[/tex]
We can write second equation y=x-4 as: [tex]-x+y=-4[/tex]
Let:
[tex]3x-y=6--eq(1)\\ -x+y=-4--eq(2)[/tex]
Now, Adding equation 1 and 2
[tex]3x-y=6\\ -x+y=-4\\--------\\2x+0y=2\\2x=2\\x=\frac{2}{2}\\x=1[/tex]
So, we get x = 1
Now, put value of x in second equation to find value of y:
[tex]y=x-4\\Put\:x=1\\y=1-4\\y=-3[/tex]
So, we get y = -3
Solving the given linear system, we get x = 1 and y = -3.
The solution set is: (1,-3)